ANALISIS KELAYAKAN FINANSIAL USAHATANI JAGUNG DI SUMARI KECEMATAN SINDUE KABUPATEN DONGGALA - Fadlun, Fadlun; Muis, Abdul; Sulaeman, Sulaeman (AGROTEKBIS, 2017)
Maize plays a part important after rice with a value of nutrition high carbohydrate. This research aims to know to eligibility of maize farming financial. This Research is executed in Sumari Village District Of Sindue Sub-Province of Donggala from April up to June 2015 with reason of that Countryside of Sumari represent one of the areas which producer of Maize. Amount of farmer of responder counted 30 farmers from totalizing population counted 103 KK pursuant to the formula of Slovin. Used Analysis Data know the target of which wish to be reached that is a Criterion Investment by using the method of Net Value present (NPV), Net Benefit Cost Ratio (Net B/C) and is Internal Rate Of Return (IRR). Result of calculation obtained NPV equal to Rp. 8,348,157.50, - indicating that investment at maize farming in Sumaria Village gives advantage equal to Rp. 8,348,157.50, - during six years according to present value by financial beneficial or competent to be labored, yielded IRR equal to 23,85% bigger than bank interest rate going into effect equal to 18%. This matter indication that maize farming in Sumaria Village District Of Sindue Sub-Province of Donggala competent to be labored because IRR bigger than bank interest rate going into effect and Net B/C obtained equal in this 2,28 matters indicate that to each, every present value of expenditure equal to Rp.1 will give benefit equal to Rp. 2,28. Key Words : Expedience, finansial, maize, producer, revenue